An Examination of Descent Place of Adiat Chapter (with an emphasis on being either Mekki or Meddani) - Qasem Faez; Emad Sadeghi; Abouzar Khier andish (پژوهش نامه معارف قرآنی, 2016)
Al Adiat is one of the Chapters of the holy Quran in which there exist differences in terms of being either a Mekki or Meddani chapter. It is thought that if the place of the Chapter’s Descent becomes clear, it is better interpreted and understood. Because of oaths to horses in war, some commentators linked the chapter to obligatory Jihad in Medina. Similarly, the narratives mentioning the Descent of this chapter after Zaat Alsalsal War regarded it as a Meddani chapter. However, by careful examinations of the style of the chapter written in the Mekki style and the accurate narratives stating its descent in Mecca, it is clarified that this chapter is Mekki, and its early verses on war, which are unrelated to jihad, descended in Medina. The content of the chapter in which issues such as Day of Resurrectionand the future life were argued and are features of Mekki Chapters is regarded as a reason for being Mekki. Also, in a reliable narrative, Imam Ali contended that Al Adiat is an account for camels in Haj. Therefore, if Al Adiat means a horse, it can be inferred that it is a warlike horse which is different from a jihadi horse in that a warlike horse was enjoying a high status among Mecca’s residents.